ANALISIS KEBIJAKAN NON TARIF TERHADAP KINERJA DAYA SAING EKSPOR PERIKANAN INDONESIA DI PASAR UNI EROPA - Andiany, Ria Munis; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
This study aims to analyze the condition of the competitiveness level of Indonesian fisheries, as well as the simultaneous and partial influence between the non tariff measure, price and Foreign Direct Investment (FDI) to the competitiveness of Indonesian fisheries processed product to the European Union market during 2005-2018. The data used is secondary data period 2005-2018. The analysis technique used is Revealed Comparative Advantage (RCA) analysis and  multiple linear regression analysis technique. The result showed that with the RCA method export of Indonesian fisheries processed product to the European Union market have competitiveness above the average level of competitiveness of the world’s fisheries processed products to the European Union market., but still lower than Vietnam and Thailand. Meanwhile, simultaneous non tariff measures, price and FDI no significant effect influence the competitiveness of fisheries to the European Union market and partially non tariff measures and FDI has a positive and significant effect, while price has a negative and significant effect to competitiveness of Indonesian fisheries processed products in the European Union market. Keywords : Non Tariff Measures, Price, FDI, RCA